Perawatan Saluran Akar Gigi Molar dengan Restorasi Mahkota Porselen Fusi Metal Diperkuat Pasak Fiber: Laporan kasus - Rosita Stefani; Ellen Winarta; Bernard Ongki Iskandar; Dina Ratnasari; Aryadi; Natalia Tjingson (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2026)
ABSTRACT Introduction: Endodontically treated teeth (ETT) are reported to have higher risk of fracture due to the loss of tooth structure and integrity following procedures such as canal preparation and obturation. Placement of a post followed by full-coverage crown is a recommended treatment option in such cases.Aim: This report aims to present the selection and design of a permanent restoration for a mandibular first molar following root canal treatment as a clinical reference. Case and Management: A 41-year-old patient who complained of pain in the lower left molar during mastication. Clinical examination revealed tooth 36 with temporary restoration, which had replaced precious permanent restoration due to patient’s discomfort. The patient experienced tenderness on percussion, while palpation and mobility were within normal limits. Radiographic examination showed a radiolucent lesion on the mesial root. Based on the history, clinical, and radiographic findings, tooth 36 was diagnosed as previously initiated. The treatment plan consisted of root canal therapy followed by fiber post placement and porcelain-fused-to-metal (PFM) crown restoration. Conclusion: Placement of fiber post and PFM successfully reinforced remaining tooth structure and restored its functions. This case highlights the importance of adequate restorative management after endodontic procedure was given in order to enhance clinical outcome. Keywords: fiber post, porcelain fused to metal, root canal treatment